VALUES IN CONSUMPTION SOCIETY. A COMPARISON OF CONSUMPTION SOCIETY IN POLAND AND IN SLOVAKIA - Byrska, Joanna Mysona (European Scientific Journal, ESJ, 2015)
The research project, ―Values in Consumption Society. A Comparison of Consumption Society in Poland and in Slovakia‖ aims to present the current perception of values among young Slovaks and Poles, as well as to show recent changes in the understanding of values in Poland and in Slovakia. This project will also attempt to make a diagnosis regarding the spread of consumption attitudes as well as the growing role and meaning of money in the life of young people at the beginning of the 21st century.